"Spin" in Plastic Surgery Randomized Controlled Trials with Statistically Nonsignificant Primary Outcomes: A Systematic Review. Issue 3 (29th November 2022) - Yuan, Morgan; Wu, Jeremy; Li, Allen; Gallo, Lucas; Chin, Brian; Murphy, Jessica; Coroneos, Christopher J.; Voineskos, Sophocles; Thoma, Achilleas
Abstract : Background: "Spin" refers to a manipulation of language that implies benefit for an intervention when none may exist. Randomized controlled trials (RCTs) in other fields have been demonstrated to employ spin, which can mislead clinicians to use ineffective or unsafe interventions. This study's objective was to determine the strategies, severity, and extent of spin in plastic surgery RCTs with nonsignificant primary outcomes. Methods: A literature search of the top 15 plastic surgery journals using MEDLINE was performed (2000 through 2020). Parallel 1:1 RCTs with a clearly identified primary outcome showing statistically nonsignificant results ( P > 0.05) were included. Screening, data extraction, and spin analysis were performed by two independent reviewers. The spin analysis was then independently assessed in duplicate by two plastic surgery residents with graduate-level training in clinical epidemiology. Results: From 3497 studies identified, 92 RCTs were included in this study. Spin strategies were identified in 78 RCTs (85%), including 64 abstracts (70%) and 77 main texts (84%). Severity of spin was rated moderate or high in 43 abstract conclusions (47%) and 42 main text conclusions (46%). The most identified spin strategy in the abstract was claiming equivalence for statistically nonsignificant results (26%); in the main text, focusing on another objective (24%). Conclusions: This study suggests that 85% of statistically nonsignificant RCTs in plastic surgery employ spin. Readers of plastic surgery research should be aware of strategies, whether intentional or unintentional, used to manipulate language in reports of statistically nonsignificant RCTs when applying research findings to clinical practice.